3.5 GHz longitudinal leaky surface acoustic wave resonator using a multilayered waveguide structure for high acoustic energy confinement. (11th June 2018) - Kimura, Tetsuya; Kishimoto, Yutaka; Omura, Masashi; Hashimoto, Ken-ya
Abstract: In this paper, the use of a structure comprising a thin LiNbO3 plate and a multilayered acoustic mirror composed of SiO2 and Pt for high-performance longitudinal leaky surface acoustic wave (LLSAW) device is proposed. The mirror is expected to offer a much higher reflectivity than that composed of SiO2 and AlN, which the authors proposed previously. The field distribution of these structures is calculated by using a finite element method. It is shown that the acoustic wave energy of the proposed structure is well confined in the vicinity of the top surface, and that leakage to the substrate is reduced. A one-port resonator is fabricated on the structure and its performance characteristics are evaluated. Owing to a high phase velocity of 6, 035 m/s, which is about 1.5 times higher than that of conventional SAWs, a large impedance ratio of 71 dB was achieved at 3.5 GHz in addition to a large fractional bandwidth of 9.5%.